2023
DOI: 10.3390/nu15030552
|View full text |Cite
|
Sign up to set email alerts
|

Joint Effect of Multiple Metals on Hyperuricemia and Their Interaction with Obesity: A Community-Based Cross-Sectional Study in China

Abstract: Metal exposures have been inconsistently related to the risk of hyperuricemia, and limited research has investigated the interaction between obesity and metals in hyperuricemia. To explore their associations and interaction effects, 3300 participants were enrolled from 11 districts within 1 province in China, and the blood concentrations of 13 metals were measured to assess internal exposure. Multivariable logistic regression, restricted cubic spline (RCS), Bayesian kernel machine regression (BKMR), and intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Model 3 was further adjusted for education, smoking, drinking, physical activity, sedentary, energy intake, carbohydrate intake, fat intake, and protein intake. Finally, the criteria under which mediation analysis can be performed are: "statistically signi cant correlation between X and M" and "statistically signi cant correlation between M and Y" [31]. Once the conditions for mediation analysis were met, we used the R language package "bruceR" to analyze the mediating role of SII in the relationship between metals and TOFAT.…”
Section: Discussionmentioning
confidence: 99%
“…Model 3 was further adjusted for education, smoking, drinking, physical activity, sedentary, energy intake, carbohydrate intake, fat intake, and protein intake. Finally, the criteria under which mediation analysis can be performed are: "statistically signi cant correlation between X and M" and "statistically signi cant correlation between M and Y" [31]. Once the conditions for mediation analysis were met, we used the R language package "bruceR" to analyze the mediating role of SII in the relationship between metals and TOFAT.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have suggested that limiting salt intake to moderate levels lowers the risk of cardiovascular events, prospective randomized controlled trials have not yet offered conclusive evidence regarding the ideal sodium intake to reduced cardiovascular events and death 22 . A recent meta-analysis revealed that the best antihypertensive medications for lowering blood pressure in salt-sensitive people were calcium channel blockers and hydrochlorothiazide 23 .…”
Section: Discussionmentioning
confidence: 99%
“…We also used g-computation analysis to explore the mixture effect of metals on TOFAT and SII. Finally, the criteria under which mediation analysis can be performed are: “statistically significant correlation between X and M” and “statistically significant correlation between M and Y” 31 . Once the conditions for mediation analysis were met, we used the R language package “bruceR” to analyze the mediating role of SII in the relationship between metals and TOFAT.…”
Section: Methodsmentioning
confidence: 99%